2009
DOI: 10.1016/j.bbmt.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

A “No-wash” Albumin-Dextran Dilution Strategy for Cord Blood Unit Thaw: High Rate of Engraftment and a Low Incidence of Serious Infusion Reactions

Abstract: Preparation of cord blood (CB) units for infusion by albumin-dextran dilution without centrifugation may be advantageous for adult patients to minimize cell loss and, unlike a bedside thaw, is still conducted in the controlled laboratory environment. Therefore, we studied CB transplantation (CBT) using this technique in 54 consecutive CBT recipients ≥20 kg. Patients [median age 42 years (range 7–66); median weight 71 kg (range 24–109)] were transplanted for high-risk hematological malignancies with ablative (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 12 publications
2
85
1
1
Order By: Relevance
“…A similar approach was recently explored and published in children and adults receiving double cord blood units. 23,24 Infusion reactions were mild and actually lower in our trial than previously reported with this technique. 23,24 We believe that this technique permits centers to choose units as low as 1 × 10 7 NC/kg when larger units are not available and still achieve favorable outcomes.…”
Section: Discussioncontrasting
confidence: 53%
“…A similar approach was recently explored and published in children and adults receiving double cord blood units. 23,24 Infusion reactions were mild and actually lower in our trial than previously reported with this technique. 23,24 We believe that this technique permits centers to choose units as low as 1 × 10 7 NC/kg when larger units are not available and still achieve favorable outcomes.…”
Section: Discussioncontrasting
confidence: 53%
“…A no-wash dilution technique for CBSC resulted in infusion reactions that required additional therapy in 65% of patients; however, no serious life-threatening events occurred. 11 The reactions were hypertension, nausea, pain, fever, hypoxia and renal impairment and were not attributed to DMSO content.…”
Section: Discussionmentioning
confidence: 99%
“…10 No relationship between DMSO and ARs in cord blood transplants has been observed. 11 High WBC concentration, especially due to granulocytes or PMNs, has been associated with increased frequency and severity of ARs. [12][13][14][15] Other risk factors include patient age and non-mononuclear cells, 13 total nucleated cell dose, 16,17 RBC content 18 and infusion technique.…”
Section: Introductionmentioning
confidence: 99%
“…Single-unit CBT is considered standard by many TCs, and comparable survival has recently been published in both pediatric and adult recipients of single-unit CBT and URD hematopoietic stem cell transplantation. 8,15 However, retrospective studies have suggested that double-unit grafts improve the likelihood of engraftment and reduce transplantation-related mortality (TRM) in adults and larger children compared with single-unit CBT controls, 10,12 and that they are associated with a reduced risk of relapse. 11,13,14,22,23 Our institutional policy is therefore to routinely use double-unit grafts, and we have achieved a cumulative incidence of sustained donor engraftment of 94% in patients with hematologic malignancies, 12 a result comparable with the engraftment reported in a large series of URD peripheral blood stem cell transplantation.…”
mentioning
confidence: 99%
“…8 In addition, promising survival has been reported for adult CBT recipients. [9][10][11][12][13][14] Recently, Eapen et al have reported comparable 2-year leukemiafree survival after single-unit CBT and 7 or 8 of 8 HLA allelematched URD peripheral blood or BM transplantation in adults. 15 Moreover, Brunstein et al have found comparable 5-year leukemiafree survival after double-unit CBT, HLA-matched related donor, and HLA-allele matched or 1-antigen mismatched URD transplantation.…”
mentioning
confidence: 99%